Relation between Topic, Image, and Translation Strategy in Metaphor and Simile Translation Found in One of Us is Next - Sihasale, Thomas Fandres; Darta, Deta Maria Sri (Universitas Dian Nuswantoro, 2025)
Metaphors and similes are significant elements in literary texts that help the author to convey his/her message. This study analyzed the topic and image of metaphors and similes in the source text, and how they were translated into the target text. The data was taken from One of Us is Next, an American novel by Karen M. McManus, and its Bahasa Indonesia translated version, Satu Permainan (One of Us Is Next). Because the data were in textual form, this research applied descriptive qualitative to examine the translation strategy that was used by the translator and the equivalence between the source and the target text. The data were arranged in the table, with descriptive explanations in each of them. This study found the patterns of the metaphor and simile: human vs human and human vs non-human in metaphor and simile, and non-human vs non-human in metaphor. The intriguing pattern found was human versus non-human, which was mostly translated literally in both Metaphor and Simile, whereas the other patterns were less.